2013
DOI: 10.1002/mc.22026
|View full text |Cite
|
Sign up to set email alerts
|

Triplex-forming oligonucleotides targeting c-MYC potentiate the anti-tumor activity of gemcitabine in a mouse model of human cancer

Abstract: Antimetabolite chemotherapy remains an essential cancer treatment modality, but often produces only marginal benefit due to the lack of tumor specificity, the development of drug resistance, and the refractoriness of slowly-proliferating cells in solid tumors. Here, we report a novel strategy to circumvent the proliferation-dependence of traditional antimetabolite-based therapies. Triplex-forming oligonucleotides (TFOs) were used to target site-specific DNA damage to the human c-MYC oncogene, thereby inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…For example, they can act as anchors to recruit DNA methylation enzymes or histone-modifying proteins to specific sites in chromatin 38 , 39 , which can, in turn, regulate gene transcription. TFOs serve as transcriptional suppressors and can downregulate gene expression in cancer 29 , 45 47 . For example, TFOs directed to a particular sequence in the Ets2 promoter can repress transcription of this gene, thereby inducing growth inhibition and apoptosis in prostate cancer 46 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, they can act as anchors to recruit DNA methylation enzymes or histone-modifying proteins to specific sites in chromatin 38 , 39 , which can, in turn, regulate gene transcription. TFOs serve as transcriptional suppressors and can downregulate gene expression in cancer 29 , 45 47 . For example, TFOs directed to a particular sequence in the Ets2 promoter can repress transcription of this gene, thereby inducing growth inhibition and apoptosis in prostate cancer 46 .…”
Section: Discussionmentioning
confidence: 99%
“… 135 So far, TFOs have not been used clinically, but it was recently reported that a TFO targeting the MYC promoter in combination with gemcitabine potentiated the antitumor activity in a mouse model. 136 …”
Section: Oligonucleotides With Anti-gene Capacitymentioning
confidence: 99%
“…Another key protein that regulates pancreatic cancer cell sensitivity to gemcitabine is c-Myc, a central transcription factor with a plethora of target genes that play roles in proliferation, mitochondrial biogenesis, and glucose metabolism. The MYC proto-oncogene is overexpressed in many types of cancer [ 9 ], including pancreatic cancer [ 10 ] where it has been shown to decrease sensitivity to gemcitabine [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%